EVALUASI TERAPI REHIDRASI DAN MENERUSKAN NUTRISI UNTUK DIARE AKUT TANPA DEHIDRASI PADA ANAK BALITA DI RSUD DI BANTUL - Ignasia Nila Siwi; Patricia Suti Lasmani; Yati Soenarto (Jurnal Kesehatan Madani Medika (JKMM), 2016)
Background: Diarrhea is one of the leading causes of death in children under five (WHO, 2013 & 2016). The main causes of infant and child deaths from diarrhea are severe dehydration (IDHS, 2012). Bantul Regency is one of the districts that has a high number of diarrhea cases in DIY. Diarrhea cases in Bantul district in 2014 were 20,729 cases or 26.87% of the total cases of diarrhea in DIY (DIY Profile, 2015). Objective: To evaluate the indicators of rehydration therapy and continue the nutrition for acute diarrhea without dehydration in children under five in Panembahan Senopati General Hospital. Method: This research is a case study with an explanatory descriptive design. The source of evidence used was documentation of medical records of patients with acute diarrhea without dehydration in children under five June-August 2016 as quantitative data, triangulation was carried out by observation, FGD and interviews as qualitative data. Results: Management of rehydration therapy and continuing food and / or breast milk still need to be improved (n = 30), namely 27% rehydration therapy and 23% continue to eat and / or breast milk no documentation due to limited documentation time but edited. Conclusion: There is a mismatch of management of rehydration therapy and continued eating and / or breast milk due to limited time in documentation.